(untitled) (Innovative professional education, 2024)
The examines the negative impact of the Russian invasion on Ukraine’s energy system and the role of renewable energy in overcoming the energy crisis. The preparation of the adult population for entrepreneurship as a strategic factor in ensuring the country’s energy independence is considered. The relationship between entrepreneurship development and stabilisation of the energy sector is analysed. The importance of educational programmes for adults in the context of forming energy sustainability and economic security of Ukraine in the context of war is emphasised.